2004
DOI: 10.1111/j.1445-6664.2004.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilities of some aquatic ferns to paddy herbicide bensulfuron methyl

Abstract: Paddy herbicides have the potential to cause adverse effects on non-target plants. Susceptibilities of some aquatic ferns ( Azolla japonica Franch. et Savat., Isoetes japonica A. Braun, Marsilea quadrifolia L. and Salvinia natans All.) and duckweeds ( Lemna minor L. and Spirodela polyrhiza Schleid.) to paddy herbicide bensulfuron methyl (BSM) were evaluated with a 20 day exposure experiment using 200 cm 2 pots. The BSM concentrations in the surface water of monitoring pots with no plants dissipated exponential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…The toxicological tests showed that M. quadrifolia is sensitive to a wide range of herbicides that have different mechanisms of action, such as the interruption of fatty acid (Aura, Clincher or pigment biosynthesis (Command), the inhibition of enzymes involved in amino acid biosynthesis (Glifosato, Gulliver, Viper) and the disruption of photosynthesis (Command)). These data agree with previous analyses conducted by Luo and Ikeda (2007) and Aida et al (2004), which suggest that several aquatic ferns are generally susceptible to herbicides at low concentrations.…”
Section: Conservation Status and Threats To Species Survivalsupporting
confidence: 92%
“…The toxicological tests showed that M. quadrifolia is sensitive to a wide range of herbicides that have different mechanisms of action, such as the interruption of fatty acid (Aura, Clincher or pigment biosynthesis (Command), the inhibition of enzymes involved in amino acid biosynthesis (Glifosato, Gulliver, Viper) and the disruption of photosynthesis (Command)). These data agree with previous analyses conducted by Luo and Ikeda (2007) and Aida et al (2004), which suggest that several aquatic ferns are generally susceptible to herbicides at low concentrations.…”
Section: Conservation Status and Threats To Species Survivalsupporting
confidence: 92%
“…Several physiological and biochemical mechanisms are involved in response of Azolla to pesticide stress. Reduction in fresh weight and dry weight was clear after five days of incubation at different concentration in ppm of endosulfan .our results are comparable to the observations made by (Aida et al, 2006) and recently done by (ElShahate et al, 2011). It is found that pesticide has an inhibitory effect on photosynthetic CO 2 assimilation and protein synthesis (Battah et al, 2001) which could be due to disturbances in nitrogen metabolism and photosynthetic activity or due to increase in protease activity (Kaushik and Venkataraman, 1983) such effects might exert much secondary effect on growth.…”
Section: Discussionsupporting
confidence: 92%
“…The removal of these insecticides from soil and aquatic systems has become a difficult problem and as a result of this, they persist in these ecosystems for a long period of time (Singh, 1988). Water bodies such as ponds, water reservoirs, aquaculture, shallow water and paddy fields are highly eutrophic and maintain large standing crops of phytoplankton's and floating plants and some aquatic fern like Azolla (Aida et al, 2006). An Azolla-Anabaena association is a favourite biofertilizer of crops, especially in rice paddy fields because of its ability to fix dinitrogen at high rates and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Among the newer herbicides, sulfonylurea herbicides are effective in controlling weeds even when applied in very small amounts (about 50 g ha −1 ), and thus they are widely used in Japan. Laboratory studies have shown that the application of bensulfuron methyl has a pronounced effect on the growth rate of the threatened aquatic ferns Azolla japonica and Salvinia natans, with a 50% inhibition (EC50) of 5.0 and 0.54 nM, respectively (Aida et al, 2004(Aida et al, , 2006. For invertebrates, laboratory studies have shown that synthetic pyrethroids and neonicotinoids, which are now widely used in Japan, are highly toxic to various invertebrate species (Tanaka et al, 2000).…”
Section: Newer Pesticidesmentioning
confidence: 99%